Futuristic decentralized clean energy networks in view of inclusive-economic growth and sustainable society. (1st August 2021) - Javid, Iqra; Chauhan, Aditya; Thappa, Sahil; Verma, S.K.; Anand, Y.; Sawhney, A.; Tyagi, V.V.; Anand, S.
Abstract: The growing demand for energy over the last few decades has increased our dependency on fossil fuel-based sources leading to significant environmental degradation and huge external debt. This article addresses the wide spectrum role of some well-planned decentralized-distributed energy networks to realize the need for comprehensive energy planning for inclusive economic growth. An extensive review of different design configurations, their implementation models and socio-economic dimensions are critically presented with solutions for clean energy deliverance. The article recommends that the objectives of uniform energy regulation and its wide range distribution should be based on some novel anticipated models, sufficient enough to fulfil energy demand and to integrate some other energy sources at minimum possible cost for a particular site. The constraints have been well identified at modelling, budgetary and implementation stages as required for uninterrupted and uniform distribution specifically to the far-reaching areas. This study has also resulted in the establishment of the statement that "Technological advancements with specific solutions coordinated through central monitoring are essential because of the fast and reliable implementation of the plan on-ground". It is also notable that, Role of different and individual stakeholders should be fixed to take an integral part in the advantageous use of decentralized energy network by analysing and utilizing locally available resources. Highlights: This article is a state of the art review on the decentralized energy system (DES). Shows wide spectrum role of well-planned decentralized-distributed energy networks. Discusses different design configurations along with socio-economic dimensions. Reflects limitations and shortcomings in integrating and implementation of DES. Identifies the barriers, contribution & limitations, implications & Policy suggestions.